Dynamic and static mechanical properties of PP/EVA blend nanocomposites: Effects of type of masterbatch preparation technique and nature of compatibilizer. (December 2021) - Tekay, Emre; Doğu, Salih; Şen, Sinan
Polypropylene (PP)/poly (ethylene-co-vinyl acetate) (EVA) nanocomposites were prepared with use of 3 wt% of organophilic halloysite nanotubes (Org-HNTs) and 3 types of compatibilizers in two steps. First, masterbatchs of EVA and the compatibilizers with the Org-HNT were prepared by two different preparation techniques; melt masterbatch (MM) and solution masterbatch (SM). The masterbatchs were then melt compounded with PP in the second step. Special attention was paid to effects of nature of compatibilizer and masterbatch preparation technique on morphology-mechanical property relationship for the composites. Poly(ethylene-vinyl acetate-carbon monoxide) (EVACO) and maleic anhydride grafted EVA (EVA-g-MA) were used as EVA-based compatibilizers which gave a homogeneous distribution of the nanotubes in the matrix and at the matrix-elastomer interphase as compared to maleic anhydride grafted PP (PP-g-MA). The both masterbatch techniques provided a core-shell morphology composed of nanotubes as core surrounded with elastomer phase as a shell, which led to higher toughness and impact resistance for the composites. Particularly, the EVACO compatibilizer provided the highest toughness, tensile modulus and impact resistance for 3% Org-HNT loaded nanocomposite produced with the SM technique. The same nanocomposite was found to act as an effective damper with an optimum modulus in a broad range of temperature and show a relatively higher creep resistance than the counterpart produced with the MMT technique. It also exhibited 66% higher scratch resistance compared to the PP/EVA blend, which makes it advantageous for the visible parts in automotive applications.